Dopamine D4 Receptor Exon III Polymorphism, Adverse Life Events and Personality Traits in a Nonclinical German Adult Sample - Reiner, Iris; Spangler, Gottfried (Neuropsychobiology, 2010)
Personality and temperament embrace a wide area of both psychological and behavioral processes which are also based on disposition. A functional polymorphism in exon III of the dopamine D4 receptor gene (DRD4) has been a highly suspect genetic marker for personality in spite of ambiguous results. The present study aimed to further elucidate the relationship between DRD4, negative life events and personality in a representative nonclinical sample. Hundred sixty-seven Germans completed the NEO Five-Factor Inventory, the Tridimensional Personality Questionnaire and the California Adult Q-Sort. A factor analysis revealed 3 factors: emotional stability, social orientation and impulsivity. DNA from buccal cells was genotyped for the DRD4 variable-number tandem-repeat exon III polymorphism with respect to presence versus absence of the DRD4 7-repeat allele. Adverse life events were assessed by means of the Adverse Life Events Scale. Men carrying the DRD4 7-repeat allele were more impulsive than those without. Male 7-repeat carriers were more emotionally instable than others, but only when they experienced a large amount of negative life events. No genotype-personality relationships were found for women. The results indicate gender-specific influences of the DRD4 gene on human behavior and invite researchers to further investigate gene-environment correlations on personality traits. © 2010 S. Karger AG, Basel.